Defining Critical Genes During Spherule Remodeling and Endospore Development in the Fungal Pathogen, Coccidioides posadasii - Mead, H. L.; Roe, C. C.; Higgins Keppler, E. A.; Van Dyke, M. C. Caballero; Laux, K. L.; Funke, A.L.; Miller, K. J.; Bean, H. D.; Sahl, J. W.; Barker, B. M. (Frontiers in Genetics, 2020)
Coccidioides immitis and C. posadasii are soil dwelling dimorphic fungi found in North and South America. Inhalation of aerosolized asexual conidia can result in asymptomatic, acute, or chronic respiratory infection. In the U.S. there are approximately 350,000 new infections per year. The Coccidioides genus is the only known fungal pathogen to make specialized parasitic spherules, which contain endospores that are released into the host upon spherule rupture. The molecular determinants involved in this key step of infection remain largely elusive as 49% of genes are hypothetical with unknown function. An attenuated mutant strain C. posadasii Δcts2/Δard1/Δcts3 in which chitinase genes 2 and 3 were deleted was previously created for vaccine development. This strain does not complete endospore development, which prevents completion of the parasitic lifecycle. We sought to identify pathways active in the wild-type strain during spherule remodeling and endospore formation that have been affected by gene deletion in the mutant. We compared the transcriptome and volatile metabolome of the mutant Δcts2/Δard1/Δcts3 to the wild-type C735. First, the global transcriptome was compared for both isolates using RNA sequencing. The raw reads were aligned to the reference genome using TOPHAT2 and analyzed using the Cufflinks package. Genes of interest were screened in an in vivo model using NanoString technology. Using solid phase microextraction (SPME) and comprehensive two-dimensional gas chromatography – time-of-flight mass spectrometry (GC×GC-TOFMS) volatile organic compounds (VOCs) were collected and analyzed. Our RNA-Seq analyses reveal approximately 280 significantly differentially regulated transcripts that are either absent or show opposite expression patterns in the mutant compared to the parent strain. This suggests that these genes are tied to networks impacted by deletion and may be critical for endospore development and/or spherule rupture in the wild-type strain. Of these genes, 14 were specific to the Coccidioides genus. We also found that the wild-type and mutant strains differed significantly in their production versus consumption of metabolites, with the mutant displaying increased nutrient scavenging. Overall, our results provide the first targeted list of key genes that are active during endospore formation and demonstrate that this approach can define targets for functional assays in future studies.